2009
DOI: 10.1051/0004-6361/200811592
|View full text |Cite
|
Sign up to set email alerts
|

A binary engine fuelling HD 87643's complex circumstellar environment

Abstract: Context. The star HD 87643, exhibiting the "B[e] phenomenon", has one of the most extreme infrared excesses for this object class. It harbours a large amount of both hot and cold dust, and is surrounded by an extended reflection nebula. Aims. One of our major goals was to investigate the presence of a companion in HD87643. In addition, the presence of close dusty material was tested through a combination of multi-wavelength high spatial resolution observations. Methods. We observed HD 87643 with high spatial r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 38 publications
2
68
0
1
Order By: Relevance
“…Other interesting objects in which a close (in projection) binary component was discovered by means of interferometry are the A[e] supergiant HD 62623 (Millour et al 2011, although this star was recently re-classified as a B8-9 Ib-II star by Borges Fernandes et al, in prep.) and the B[e]SG candidates HD 87643 (Millour et al 2009) and V921 Scorpii (=CD-42 11721; Kraus et al 2012). Only the first two have been found to display CO band emission, and detailed modeling will determine the kinematics of the CO gas and possibly help to distinguish between the scenarios of circumstellar or circumbinary origin (Muratore et al, in prep.…”
Section: Circumbinary Disk Of Gg Carmentioning
confidence: 99%
“…Other interesting objects in which a close (in projection) binary component was discovered by means of interferometry are the A[e] supergiant HD 62623 (Millour et al 2011, although this star was recently re-classified as a B8-9 Ib-II star by Borges Fernandes et al, in prep.) and the B[e]SG candidates HD 87643 (Millour et al 2009) and V921 Scorpii (=CD-42 11721; Kraus et al 2012). Only the first two have been found to display CO band emission, and detailed modeling will determine the kinematics of the CO gas and possibly help to distinguish between the scenarios of circumstellar or circumbinary origin (Muratore et al, in prep.…”
Section: Circumbinary Disk Of Gg Carmentioning
confidence: 99%
“…To match the data with the model, we interpolated the parameters for other wavelengths using cubic spline interpolation. The global optimum of the fit was found using a set of simulated annealing algorithms complemented by standard gradient descent algorithms (see Millour et al 2009, for a first application of this approach). A model with three spots (i.e., performing a fit with a uniform disk, a Gaussian disk, and three spots) significantly enhance the fit (χ 2 ≈ 25), especially for the visibilities and closure phases up to spatial frequency of ≈240 cycles/arcsec.…”
Section: Geometrical Toy Modelsmentioning
confidence: 99%
“…Oudmaijer et al (1998) argue that HD 87643 is an evolved B[e] star (see also Kraus 2009). Millour et al (2009) based on AMBER-VLTI observations reported a close companion at 34 mas.…”
Section: Introductionmentioning
confidence: 99%